2003
DOI: 10.1182/blood-2003-03-0877
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell transplantation for progressive multiple sclerosis: failure of a total body irradiation–based conditioning regimen to prevent disease progression in patients with high disability scores

Abstract: There were 21 patients with rapidly progressive multiple sclerosis (MS) treated on a phase 1/2 study of intense immune suppressive therapy and autologous hematopoietic stem cell (HSC) support with no 1-year mortality. Following transplantation, one patient had a confirmed acute attack of MS. Neurologic progression defined by the expanded disability status scale (EDSS) did not increase in disability by 1.0 or more steps in any of 9 patients with a pretransplantation EDSS of 6.0 or less. In 8 of 12 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
121
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 190 publications
(133 citation statements)
references
References 43 publications
7
121
0
5
Order By: Relevance
“…Either agent may cause dose-dependent neurotoxicity, aggravate MS associated CNS damage or prevent the ability of the CNS to recover from an insult by damaging the endogenous regenerative mechanism in the brain. HSCT after total body irradiation has been associated with poorer MS outcomes [14,45] and this could be attributed to these mechanisms. In the future, a risk-adapted treatment approach could tailor the optimum conditioning regimen dose intensity to the risks of neurotoxicity and to the aggressiveness of the MS.…”
Section: Lesson 3: Cns Toxicity Of Very High-dose Regimens May Adversmentioning
confidence: 99%
See 4 more Smart Citations
“…Either agent may cause dose-dependent neurotoxicity, aggravate MS associated CNS damage or prevent the ability of the CNS to recover from an insult by damaging the endogenous regenerative mechanism in the brain. HSCT after total body irradiation has been associated with poorer MS outcomes [14,45] and this could be attributed to these mechanisms. In the future, a risk-adapted treatment approach could tailor the optimum conditioning regimen dose intensity to the risks of neurotoxicity and to the aggressiveness of the MS.…”
Section: Lesson 3: Cns Toxicity Of Very High-dose Regimens May Adversmentioning
confidence: 99%
“…However, it was observed that these patients (with an Expanded Disability Status Scale [EDSS] score≥6.0) had poor outcomes compared with patients who entered HSCT with less disability [14]. A review of data from the EBMT registry that stratified patients by age and duration of MS, showed markedly better outcomes for recipients who were younger than 40 years of age and had been diagnosed within the last 5 years compared with older patients who had longstanding MS [18].…”
Section: Lesson 4: Hsct Is More Likely To Be Effective For Ms Patientmentioning
confidence: 99%
See 3 more Smart Citations